MORAL HAZARD DALAM PERILAKU EKONOMI MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Dea, Stephanie Vania; Witarsa, Witarsa; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Ease of access to the internet and the increasing development of technology will lead to consumer behavior in people's lives. This ease of access will increase a person's interest in buying something, whether based on fulfilling a need or just based on interest. This is also influenced by the person's thought patterns and behavior. The main problem studied in writing this thesis is moral hazard behavior that occurs in students who are far from their parents. Taking as an object the students of the economic education study program, Faculty of Teacher Training and Education, Tanjungpura University, Pontianak. This research uses qualitative methodology. Qualitative data was obtainedfrom interviews with five students who, when completing college, lived in rented houses and lived independently or away fromtheir parents. Non-partisan observations and documentation were carried out to see the moral hazard behavior carried out. Data analysis was carried out by conducting narrative analysis on interview transcripts. In this research it can be concluded: First, that the economic behavior of students at FKIP UNTAN's economic education is still very consumptive with the finances provided coming from their parents. Second, there is still information asymmetry between owners and users, causing users to use the money given carelessly